EFFECT OF BIOFILM WITH BIOFERTILIZER OF Pseudomonas fluorescens AND Rhizobium leguminosarum ,CHEMICAL FERTILIZER LEVEL AND ADDATION TECHNIQUE ON SOME GROWTH AND YIELD TRAITS OF WHEAT(Triticum asetivum L.) - & Jasim, Abdul -Ratha (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This Research was performed to evaluate the efficiency of Biofilm Biofertilizer produced from local isolates of Pseudomonas fluorescens, Rhizobium leguminosarum, with two addition technique include with bentonite as carrier and with liquid inoculant(without carrier) and three levels of chemical fertilizers (zero,25,50)% of recommendation on some growth and yield traits of wheat variety Rashid Biofilm Biofertilizer and chemical fertilizer affect significantly on all growth characters of wheat plant, Bentonite gave the best result compare with liquid inoculant, use of Biofilm Biofertilizer with 50% of the chemical fertilizer recommendation gave highest growth and yield of wheat .The duple Biofilm Biofertilizer of P. fluorescens plus R. leguminosarum was superior in enhancing growth and yield of wheat plant .The treatment of Biofilm Biofertilizer of P. fluorescens and R. leguminosarum with Bentonite and 50 chemical fertilizer recommendation gave45.89cm2, 47.77 spad,70.00 gm,39.81mgN g-1 4.931mgP g-135.471mgK g- 1 of leaf area, chlorophyll content, weight of 1000 grains, Nitrogen, Phosphorus, Potassium uptake in the vegetative part respectively.of plant